A Gemini Quaternary Ammonium Poly (ether ether ketone) Anion‐Exchange Membrane for Alkaline Fuel Cell: Design, Synthesis, and Properties. Issue 12 (24th October 2014) - Si, Jiangju; Lu, Shanfu; Xu, Xin; Peng, Sikan; Xiu, Ruijie; Xiang, Yan
Abstract To reconcile the tradeoff between conductivity and dimensional stability in AEMs, a novel Gemini quaternary ammonium poly (ether ether ketone) (GQ‐PEEK) membrane was designed and successfully synthesized by a green three‐step procedure that included polycondensation, bromination, and quaternization. Gemini quaternary ammonium cation groups attached to the anti‐swelling PEEK backbone improved the ionic conductivity of the membranes while undergoing only moderate swelling. The grafting degree (GD) of the GQ‐PEEK significantly affected the properties of the membranes, including their ion‐exchange capacity, water uptake, swelling, and ionic conductivity. Our GQ‐PEEK membranes exhibited less swelling (≤40 % at 25–70 °C, GD 67 %) and greater ionic conductivity (44.8 mS cm−1 at 75 °C, GD 67 %) compared with single quaternary ammonium poly (ether ether ketone). Enhanced fuel cell performance was achieved when the GQ‐PEEK membranes were incorporated into H2/O2 single cells.